Biologically active quinoline and quinazoline alkaloids part I. Issue 3 (13th September 2017) - Shang, Xiao‐Fei; Morris‐Natschke, Susan L.; Liu, Ying‐Qian; Guo, Xiao; Xu, Xiao‐Shan; Goto, Masuo; Li, Jun‐Cai; Yang, Guan‐Zhou; Lee, Kuo‐Hsiung
Abstract: Quinoline and quinazoline alkaloids, two important classes of N ‐based heterocyclic compounds, have attracted tremendous attention from researchers worldwide since the 19th century. Over the past 200 years, many compounds from these two classes were isolated from natural sources, and most of them and their modified analogs possess significant bioactivities. Quinine and camptothecin are two of the most famous and important quinoline alkaloids, and their discoveries opened new areas in antimalarial and anticancer drug development, respectively. In this review, we survey the literature on bioactive alkaloids from these two classes and highlight research achievements prior to the year 2008 (Part I). Over 200 molecules with a broad range of bioactivities, including antitumor, antimalarial, antibacterial and antifungal, antiparasitic and insecticidal, antiviral, antiplatelet, anti‐inflammatory, herbicidal, antioxidant and other activities, were reviewed. This survey should provide new clues or possibilities for the discovery of new and better drugs from the original naturally occurring quinoline and quinazoline alkaloids.